Upaya Peningkatan Perekonomian Petani dengan Penerapan Branding Green Agriculture di Kota Batu - Aryntika Cahyantini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to examine the impact of implementing green agriculture branding on improving the economy of farmers in Batu City, evaluating the economic impact of implementing green agriculture branding on farmers' income and market access in Batu City, Green agriculture branding promotes environmentally friendly sustainable agricultural practices, increasing added value agricultural products on the market. By using qualitative methods through in-depth interviews, field observations, and document analysis, this research shows that green agriculture branding can increase consumer awareness, expand market access, and increase farmers' income in Batu City. Apart from that, the adoption of this branding also has a positive impact on environmental sustainability and food security in the area.